1993
DOI: 10.1029/92jd02162
|View full text |Cite
|
Sign up to set email alerts
|

The seasonal variation of nonmethane hydrocarbons in the free troposphere over the North Atlantic Ocean: Possible evidence for extensive reaction of hydrocarbons with the nitrate radical

Abstract: Detailed observations have been made of the seasonal variation in concentration of a wide range of nonmethane hydrocarbons over the North Atlantic Ocean in air with a predominantly polar maritime origin. The results bear out many of the findings of our previous studies [Za 'ghtman et al., 1990] with the observation of a concentration maximum in the winter and a minimum in the summer. The more recent results indicate that the amplitude of the seasonal cycle is remarkably constant. Also the total concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
94
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(100 citation statements)
references
References 25 publications
(20 reference statements)
5
94
0
Order By: Relevance
“…CO emissions to the atmosphere are dominated by mobile combustion sources (Parrish, 2006). With fairly uniform emissions year round, the observed seasonal variations in CO reflect the efficiency of its removal via OH photooxidation (Penkett et al, 1993;Jobson et al, 1994). At TF the mean winter diurnal cycle of CO had a 13% drop in the mixing ratio between 06:00 (232 ppbv) and 14:00 h (202 ppbv, Fig.…”
Section: Aromatic Compounds -Toluene:benzene Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“…CO emissions to the atmosphere are dominated by mobile combustion sources (Parrish, 2006). With fairly uniform emissions year round, the observed seasonal variations in CO reflect the efficiency of its removal via OH photooxidation (Penkett et al, 1993;Jobson et al, 1994). At TF the mean winter diurnal cycle of CO had a 13% drop in the mixing ratio between 06:00 (232 ppbv) and 14:00 h (202 ppbv, Fig.…”
Section: Aromatic Compounds -Toluene:benzene Ratiomentioning
confidence: 99%
“…This diverse group of compounds is of interest in the troposphere because of their role in ozone (O 3 ) production, aerosol formation and controls on regional air quality. While long-term records of VOCs exist (e.g., Penkett et al, 1993;Jobson et al, 1994;Goldstein et al, 1995;Thijsse et al, 1999;Solberg et al, 2001;Gautrois et al, 2003;Yang et al, 2005;Reiss, 2006;Simmonds et al, 2006;Lee et al, 2006;Qin et al, 2007;Sive et al, 2007;Nguyen et al, 2009), the measurements rely on conventional methods such as gas chromatography with hourly time resolution at best. Although these records provide a wealth of information, proton transfer reaction-mass spectrometry (PTR-MS) offers greatly improved time resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Penkett et al [1993] proposed the presence of NO3 to explain the observed ratio of hydrocarbons in the free troposphere at high latitudes. During winter, branched chain alkanes are removed more rapidly than straight chain alkanes, which could be explained by an NO3 concentration of about 20 ppt during a period when the OH chemistry is less dominant [Penkett et al, 1993].…”
Section: Introductionmentioning
confidence: 99%
“…The principle of the analytical system was adapted from Penkett et al [1993]. Prior to analysis, a 1-2 L air sample was preconcentrated on a liquid nitrogen cold trap packed with glass beads at a freezing temperature between 88 and 90 K in the N 2 vapor just above the liquid level (sample flow 33.33 mL/min).…”
Section: Introductionmentioning
confidence: 99%